How does human capital affect food security? A perspective of specialization - Jin, Huishuang; Liu, Hui (Frontiers in Public Health, 2025)
The world is facing a food crisis and the goal of zero hunger is facing increased uncertainty. Promoting the transition from traditional to modern agriculture is important for improving agricultural productivity. Human capital is the central factor in driving the transformation of agricultural modernization. Agricultural specialization, as an important symptom of agricultural modernization, is closely linked to the human capital of the rural workforce. And, previous studies on food security have focused mainly on the area of food crops planted. Changes in the cropping structure within food crops have been neglected, and exploration from the perspective of specialized operations can fill this gap. And, few studies have integrated human capital levels with the development of agricultural social services. Therefore, the study uses large-scale micro-survey data representative of China, adopts the HHI to measure agricultural specialization, and empirically analyzes the impact of human capital on agricultural specialization and the role played by the level of agricultural socialization services in this process based on models such as OLS. Studies have shown that the human capital level of Chinese farmers is low, and there is still much room for improvement in the degree of agricultural specialization. The regression results show that human capital contributes significantly to agricultural specialization. The mechanism test show that human capital can promote the specialization by enhancing the agricultural social services. The impact of human capital on specialized operations varies significantly across regions, business scales, land transfer practices, and social network conditions. Therefore, we need to strengthen investment in the level of rural human capital and accelerate the training of new professional farmers. Agricultural infrastructure should be increased and the agricultural service supply system should be improved. Effectively strengthening the coverage of agricultural services and improving the ability of agricultural socialized service organizations to link up with and lead farmers. In addition, land transfers and moderate-scale operations should be promoted, thereby accelerating the process of agricultural modernization.